Literasi Digital Taman Baca Pelita Di Kota Tanjung Pura Kabupaten Langkat - Kustoro Budiarta; Dede Ruslan; Faisal Faisal; Sriadhi Sriadhi; Ahmad Hidayat (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The low participation in children's education and the high drop out rate were social problems for the community in Tanjung Pura City. There fore, Pelita reading park was established as an effort to solve this problem. However, in its operation there were several problems faced including: 1) the lack of ability and knowledge of managers in the management of reading park documentation, 2) the service was still manual, 3) most of the dominant reading park activities were in the form of reading books and story telling, 4) the absence of mobile facilities. to be used as a means of service and mobile socialization, 5). lack of facilities and infrastructure. 6) limited used of information technology. The solutions offered were in the form of: assisting partners in building management of reading park based on information systems, designing tools (gerobak pintar) and preparing reading park development programs. The method of activity carried out is mentoring partners to improve the management of reading park so that they have the ability to manage reading park based on information technology and design tools in the form of smart carts. The results of this activity were 1) There was an increase in commitment and a sense of shared responsibility between the manager and the surrounding community as indicated by the increase in the number of the management team to 11 people, 2) an increase in the expertise and skills of partners in reading park documentation management. 3) the availability of gerobak pintar suitable for storing collections of reading materials, 4) the existence of an application system for managing collections of reading [ark based on information technology and 5) increasing public interest in using the Pelita reading park as a means of learning and reading.